2007
DOI: 10.1038/sj.bjc.6604074
|View full text |Cite
|
Sign up to set email alerts
|

Activity of endovesical gemcitabine in BCG-refractory bladder cancer patients: a translational study

Abstract: Intravesical gemcitabine (Gem) has shown promising activity against transitional cell carcinomas (TCC) of the bladder, with moderate urinary toxicity and low systemic absorption. The present phase II study evaluated the activity of biweekly intravesical treatment with Gem using a scheme directly derived from in vitro preclinical studies. Patients with Bacille Calmette-Guérin (BCG) -refractory Ta G3, T1 G1-3 TCC underwent transurethral bladder resection and then intravesical instillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
1
18
1
Order By: Relevance
“…Additional phase I/II studies [48][49][50] of intravesical gemcitabine published this year confirm these results. One showed that 13 out of 28 (46%) patients with recurrent bladder tumors had a complete response to four weekly instillations [50].…”
Section: Intravesical Therapysupporting
confidence: 75%
“…Additional phase I/II studies [48][49][50] of intravesical gemcitabine published this year confirm these results. One showed that 13 out of 28 (46%) patients with recurrent bladder tumors had a complete response to four weekly instillations [50].…”
Section: Intravesical Therapysupporting
confidence: 75%
“…This is lower than in the recent Phase II clinical trial comparing salvage intravesical gemcitabine (33% progression) vs. additional induction BCG (37.5% progression) in patients with recurrent NMIBC despite BCG at 2 years follow-up [11]. The rate of cystectomy was 62% at 5 years which is higher than previously published clinical trials which range from 33% to 56% at a follow-up of 1.5 to 3 years [11][12][13][14][15]. The differences are largely attributable to the fact that in our series we assumed perfect compliance and follow-up as well as strict adherence to NCCN guidelines, which are more aggressive than real-world settings.…”
Section: Discussioncontrasting
confidence: 47%
“…The study population of 1300 virtual patients is significantly higher than most published series on BCG refractory patients which range from 20-100 patients [11][12][13][14][15]. Our virtual series contained 58% of patients with clinical stage T1 urothelial carcinoma prior to randomization which falls within the range of previous BCG failure trials where 47%-78% had cT1 tumors [11,15].…”
Section: Discussionmentioning
confidence: 94%
“…Finally, Gunelli et al 25 presented a phase 2 study evaluating the activity of biweekly intravesical treatment with gemcitabine. Patients with BCG-refractory Ta-1G3 non-muscle-invasive BC underwent TUR of the bladder and then intravesical instillation with 2000 mg diluted in 50 mL saline solution on Days 1 and 3 for 6 consecutive weeks.…”
Section: Toxicitymentioning
confidence: 99%